The scales of personal freedom. Theoretical foundation, structure and initial validation of the PKW questionnaire - PRUSIŃSKI, TOMASZ (Studia Psychologica: Theoria et praxis, 2014)
Empirical research on the phenomenon of freedom in psychology have complicated history. Freedom is a subject hard to define in psychology and operationalization of this notion faces with many difficulties. This article presents the tool which is regarded as the base for the exploration of the concept of freedom: the questionnaire Private Conceptions of Freedom. The phenomenological-contextual approach, established by Mudyń and Westcott, was the groundwork to construct this questionnaire. The psychometric evaluation of the questionnaire Private Conceptions of Freedom, both in terms of reliability and validity, was satisfactory.